Writing Silica Structures in Liquid with Scanning Transmission Electron Microscopy. Issue 5 (10th September 2014) - van de Put, Marcel W. P.; Carcouët, Camille C. M. C.; Bomans, Paul H. H.; Friedrich, Heiner; de Jonge, Niels; Sommerdijk, Nico A. J. M.
<x xml:space="preserve">Abstract</x> Silica nanoparticles are imaged in solution with scanning transmission electron microscopy (STEM) using a liquid cell with silicon nitride (SiN) membrane windows. The STEM images reveal that silica structures are deposited in well‐defined patches on the upper SiN membranes upon electron beam irradiation. The thickness of the deposits is linear with the applied electron dose. Scanning electron microscopy (SEM) and atomic force microscopy (AFM) demonstrate that the deposited patches are a result of the merging of the original 20 nm‐diameter nanoparticles, and that the related surface roughness depends on the electron dose rate used. Using this approach, sub‐micrometer scale structures are written on the SiN in liquid by controlling the electron exposure as function of the lateral position.